HAMBATAN GURU DALAM PEMANFAATAN PLATFORM MERDEKA MENGAJAR DI SDN 187/I TERATAI - Wini Oktaviana; Faizal Chan; Hendra Budiono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify and describe the obstacles faced by teachers in utilizing the Merdeka Mengajar Platform (PMM) at SDN 187/I Teratai. With the introduction of the independent curriculum, it is important to understand the challenges faced by teachers in implementing this educational technology. This study is expected to provide insight for schools and the government in formulating more effective strategies to support teachers in the learning process. The method used in this study is a qualitative approach with data collection techniques through in-depth interviews and observations of grade I to VI teachers and the principal. Researchers conducted data analysis using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The research participants consisted of teachers who were directly involved in the use of PMM, so that the data obtained could provide a comprehensive picture of the existing obstacles. The results of the study showed that there were several significant obstacles faced by teachers, including limited technological competence, lack of understanding of PMM features, and time constraints in implementing educational administration. In addition, teacher motivation and acceptance of the use of PMM are also important factors that influence the effectiveness of the use of this platform. The conclusion of this study confirms that to improve the quality of learning at SDN 187/I Teratai, collaborative efforts are needed between teachers, principals, and other related parties to overcome these obstacles.